Schizophrenia: What Non-Psychiatrist Physicians Need to Know - Queirós, Tiago Pinto (2019)
Schizophrenia is a disabling and severe mental illness that affects all social classes and racial and ethnic groups, spreading across every part of the world. It’s more frequent in males and it usually manifests itself in late adolescence or early adulthood and its early detection by all clinicians is important so that there is a proper referral to specialized psychiatric care. This article intends to update the knowledge regarding the diagnosis, treatment and prognosis of schizophrenia, with an emphasis on the warning signs for a timely referral to psychiatric evaluation. We conducted a literature search across through articles available in databases of scientific articles but also in scientific and technical books specialized in the field of schizophrenia. The clinical presentation of this illness is heterogeneous and complex, with a typical evolution based on several episodes of acute decompensation requiring hospitalization. The diagnosis of schizophrenia relies on some key symptoms, and the various international diagnostic criteria vary in relation to the temporal window with productive symptomatology required to establish a diagnosis. The prognosis is variable, not always deteriorating and is all the better when the treatment is started as early as possible. Treatment requires a multidisciplinary approach and is based primarily on antipsychotic drugs. This medication although very effective for the typical symptoms of this illness, entails some adverse effects with medical consequences that are important in the clinical practice of all doctors of other specialties.